Relationship of the aggregation of cardiovascular risk factors in the parasympathetic modulation of young people with type 1 diabetes - da Silva, Anne Kastelianne França [UNESP]; Christofaro, Diego Giulliano Destro [UNESP]; Vanzella, Laís Manata [UNESP]; Vanderlei, Franciele Marques [UNESP]; Laurino, Maria Júlia Lopez [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (MDPI, 2019)
Background and objectives: In healthy individuals, autonomic alterations are associated with the aggregation of cardiovascular risk factors. However, in individuals with type 1 diabetes, who are known to present autonomic alterations, mainly characterized by a reduction in parasympathetic modulation, these associations have not yet been investigated. We assess whether the aggregation of cardiovascular risk factors influences parasympathetic indices of heart rate variability in young people with type 1 diabetes. Materials and methods: This cross-sectional study included 39 individuals with type 1 diabetes (22.54 ± 4.31), evaluated in relation to the risk factors: blood pressure, fat percentage, and resting heart rate. For heart rate variability analysis, heart rate was recorded beat-to-beat using a cardio frequency meter (PolarS810i) for 30 min with the volunteers in dorsal decubitus. The parasympathetic heart rate variability indices were calculated: rMSSD, pNN50, high frequency (HF) n.u (normalized units), SD1, 2LV, and 2ULV. Data collection was carried out in 2014 and analyzed in 2017. Results: Individuals with two aggregate risk factors present a reduction in the values of the indices that reflect parasympathetic autonomic modulation compared to individuals without the risk factors analyzed, regardless of sex and age. Conclusion: In young people with type 1 diabetes, the aggregation of cardiovascular risk factors is associated with parasympathetic autonomic impairment.
Keywords: Autonomic nervous system; Diabetes mellitus; Risk factors; Type 1; Young adult